New venture creation - Timmons, Jeffry A.
New Venture Creation: Entrepreneurship for the 21st Century is about the actual process of getting a new venture started, growing the venture, successfully harvesting it, and starting again. It continues to be the product of experience and considerable research in the fieldrooted in real-world application and refined in the classroom. The design and flow of the book are aimed at creating knowledge, skills, and awareness. In a pragmatic waythrough text, case studies and hands-on exercisesstudents are drawn in to discover critical aspects of entrepreneurship, and what levels of competencies, know-how, experience, attitudes, resources and networks are required to pursue different entrepreneurial opportunities